Risk factors and decision criteria for intensive chemotherapy in older patients with acute myeloid leukemia - Malfuson, Jean-Valere; Etienne, Anne; Turlure, Pascal; de Revel, Thierry; Thomas, Xavier; Contentin, Nathalie; Terre, Christine; Rigaudeau, Sophie; Bordessoule, Dominique; Vey, Norbert; Gardin, Claude; Dombret, Herve; et al. (Haematologica (Roma), 2008)
1 Departments of Hematology, Hôpital dInstruction des Armées, Clamart 2 Institut Paoli Calmettes, Marseille 3 Centre Hospitalier Universitaire, Limoges 4 Hôpital Edouard Herriot, Lyon 5 Centre Léon Becquerel, Rouen 6 Hôpital Mignot, Versailles 7 Hôpital Avicenne, Assistance Publique, Hôpitaux de Paris (AP-HP), University Paris 13, Bobigny 8 Hôpital Saint-Louis, AP-HP, University Paris 7, Paris, France Correspondence: Hervè Dombret, Department of Hematology, Hôpital Saint-Louis, 1 avenue Claude Vellefaux, 75010 Paris, France. E-mail: herve.dombretatsls.aphp.fr Background: There is a need for standardization of treatment decisions in older patients with acute myeloid leukemia. The aim of the present study was to analyze the decisional value of poor risk factors in 416 elderly patients treated in the ALFA-9803 trial in order to derive a decisional index. Design and Methods: Standard multivariate analysis was used to identify risk factors for overall survival. Risk factors were then considered as good decision tools if associated with a frequency >10% and a false positive rate <10% in predicting overall survival as poor as observed after low-dose cytarabine therapy (25% survival or less at 12 months). Results: Among six independent risk factors (age, performance status, white blood cell count, hematopoietic cell transplantation comorbidity index, infection at baseline, and cytogenetics), cytogenetics was the only potent, independent decision tool. High hematopoietic cell transplantation comorbidity index scores or infections were found too rarely to guide further decisions. The three other factors (age, performance status, and white cell count) needed to be combined to provide a good specificity. The proposed decisional index, therefore, included high-risk cytogenetics and/or the presence of at least two of the following criteria: age 75 years, performance status 2, and white cell count 50 x 10 9 /L. This simple two-class decisional index, which was validated in an independent patient set, enabled us to discriminate 100 patients (24%) who had an estimated overall survival of only 19% at 12 months, with a good 9% false positive rate. Conclusions: We propose waiting for cytogenetic information before making treatment decisions in elderly patients with acute myeloid leukemia. Those patients with unfavorable cytogenetics, as well as patients with at least two of the following features, age 75 years, performance status 2, and white cell count 50 x 10 9 /L, should not be considered for standard intensive chemotherapy (ClinicalTrials.gov identifier: NCT00363025 ). Key words: elderly, acute myeloid leukemia, prognosis, risk factors, decision criteria.